Adhesion molecule-modified biomaterials for neural tissue engineering - Rao, Shreyas S.; Winter, Jessica (Frontiers in Neuroengineering, 2009)
Adhesion molecules (AMs) represent one class of biomolecules that promote central nervous system regeneration. These tethered molecules provide cues to regenerating neurons that recapitulate the native brain environment. Improving cell adhesive potential of non-adhesive biomaterials is therefore a common goal in neural tissue engineering. This review discusses common AMs used in neural biomaterials and the mechanism of cell attachment to these AMs. Methods to modify materials with AMs are discussed and compared. Additionally, patterning of AMs for achieving specific neuronal responses is explored.